Pendampingan Desain Tugas Pembelajaran Bahasa Inggris Berbasis Rais bagi Guru-Guru Bahasa Inggris yang Menempuh Studi Magister - Yudhi Arifani; Sri Suyanti; Like Ayu Saputri (Jurnal SOLMA, 2023)
Background: So far, English teachers' design of English learning assignments is routine in nature so they cannot help optimize students' English skills. This community service program is implemented to help increase the professionalism of English teachers who are currently pursuing a master's program in English education from various schools in East Java using RAIS principles. Methods: Through the FGD method, mentoring, and workshops on compiling English assignments were carried out for one semester which 48 English teachers from various schools attended. Results: The results obtained are the understanding of the RAIS concept and the production of various RAIS-based English learning task models that have been implemented in various schools in East Java. Given the significance of assignments in learning, there is a constant need to improve teacher proficiency in assignment design.